Produktivitas Sapi Bali Betina dan Hasil Persilangannya dengan Limousin dan Simmental yang di Pelihara Berbasis Pakan Hijauan di Kabupaten Keerom Papua - Kocu, N.; Priyanto, R.; Salundik, Salundik; Jakaria, Jakaria (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
Development of cattle in the Papua region still faces many obstacles, particularly the limited number of cattle population and the quality of the animal dominated by bali cattle. This study aimed to evaluate the productivity of bali cattle and their crosses with limousin and simental through artificial insemination. This study was carried out on December 2016 to February 2017 in the Arso and Skanto Districts, Keerom Regency, Papua. Ninty four heads of used in this study, comprising 57 bali catsle, 18 bali x limousin and 19 bali x simmental crosses through artificial insemination programe. Parameters vanahle included reproduction characteristics, body weight and linear body measurement. The observation were conducted of calf (<12 month), young (13-24 month) and adult animal(>25 month). The results indicated that the female bali cattle and their crosses with limousin and simmental raised on forage based feed showed different reproduction and production perfomances. The cross bred cow (bali x limousin and bali x simmental) tended to have longer age at first mating, higher service per conception and lower calving rate. Based on forage feed, the cross bred cow had significantly (P<0.05) higher body weight and body frame size, particularly body weght, hip height, body lengt and heart girh at adult age. In general, the crosses between bali and limousin or simmental for cow-calf production could be developed on a forage based feed at Keerom District, Papua.